Post-covid 19 lockdown effects in EFL 3rd graders early writing skills at an elementary school in Guayaquil. - Mendieta Guamanquishpe, Pablo Andrés (2022)
This research work is a descriptive study regarding handwriting issues among third graders while they were receiving EFL writing lessons in a bilingual elementary school once they returned to face-to-face instruction after the pandemic lockdown in 2022. Bibliographic research was carried out on the topics of early literacy and fine motor skills. Twenty-five female students were subject of qualitative observation, and a handwriting skills test adapted from three different sources was also applied. After the analysis was conducted, several difficulties were discovered, including the following: keeping in the boundaries of the writing and coloring lines when writing a text or drawing a shape; usage of uniform sizing of letters; uniform spacing between letters; problems with copying entire words without frequent glancing at the board, among others. Finally, a handwriting recovery proposal was designed to train students in fine motor skills, visual perception, eye-hand coordination, and joined-handwriting scheme.